PELATIHAN PEMBUATAN BLOGSPOTUMKM WARGA DESA DOHO KABUPATEN MADIUNMENGGUNAKAN SMARTPHON - Pradityo Utomo; Dwi Nor Amadi; Setiyo Daru Cahyono (P3M Politeknik Negeri Malang, 2025)
The training on creating UMKM Blogspots aims to help rural communities improve their economy. Local community potential can be marketed digitally. Digital marketing can save capital and expand market reach. Digital marketing can utilize blogspots. Blogspot is a platform with several advantages. Namely, it is easy to access, does not require significant costs, and people can learn it easily. Through this training, people can manage blogspots to promote Micro, Small, and Medium Enterprises (UMKM) products. Some of these products include agricultural products, handicrafts, and regional food products. This training activity provides education on the use of blogspots as a means of online marketing media. In addition, the training also studies basic e-commerce techniques, such as product photos, writing descriptions, and content management. This aims to optimize blogspots as a means of promotion so that product marketing has a broader reach. UMKM blogspots can increase community income and foster sustainable digital skills. UMKM blogspots can be a flexible and easy-to-manage promotional tool that people can use independently. This training produces personal UMKM blogspots. More than half of the forum participants can understand the training material. This proves that UMKM owners have quite a lot of enthusiasm for learning Blogspot.